Indihome Witel Bekasi Customer Relations Strategy in Maintaining Customer Loyalty Through the High Value Customer (HVC) Program - Aswad Ishak; Aziza Kistikiwari Putri (Jogjakarta Communication Conference (JCC), 2023)
Today's Internet network is a necessity for some people. PT Telkom Indonesia as one of the internet service provider companies in Indonesia is trying to maintain customer loyalty so that customers are loyal to the company's products. Therefore, this paper will discuss the customer relations strategy that was built to build a sense of customer loyalty to the company using the case study research method. The results of this study indicate that PT Telkom builds a customer relations strategy by creating a High Value Customer (HVC) program as an effort to maintain customer loyalty, with this program the company gives appreciation to every loyal customer by getting special benefits as an effort to build customer empathy for the company.